Diffusion Tensor Imaging for Quantitative Assessment of Anterior Cruciate Ligament Injury Grades and Graft. Issue 5 (20th August 2020) - Liu, Shuyi; Liu, Jing; Chen, Weicui; Zhang, Lu; Wu, Shanshan; Wang, Fei; Pan, Jianke; Luo, Minghui; Liu, Xian; Zhang, Shuixing
Abstract : Background: As the need for quantitative assessment of anterior cruciate ligament (ACL) injuries and ACL graft increases, diffusion tensor imaging (DTI) becomes a more valuable measuring tool. However, DTI changes in differing injury grades of ACL and longitudinal graft remain unclear. Purpose: To investigate the diagnostic performance of DTI in quantitatively assessing ACL injury severity and the development of ACL grafts within 6 months of surgery. Study Type: A cohort study. Subjects: Thirty‐five patients diagnosed with grades I–IV ACL injuries and 20 volunteers as controls were recruited. Field Strength/Sequence: T1 ‐weighted, T2 ‐weighted, proton density (PD)‐weighted, and DTI at 3.0T MRI. Assessment: ACL injury grades in arthroscopic images and DTI quantitative data were evaluated from July 2016 to July 2018. Statistical Tests: Chi‐square test, analysis of variance, Spearman correlation analysis, and receiver operator characteristic (ROC) curves. Results: Both fractional anisotropy (FA) ( r = −0.898, P < 0.05) and apparent diffusion coefficient (ADC) ( r = 0.851, P < 0.05) were significantly correlated with the severity of ACL injuries. The area under the curve (AUC) values for differentiation between low‐ and high‐grade ACL injuries with FA and ADC were 0.973 and 0.963, respectively. Although there were no significant differences in FA ( P > 0.05) and ADC ( P > 0.05) between grades I and II ACL injuries or in ADC ( P > 0.05) between grades III and IV, there were significant differences in FA and ADC between two grades ( P < 0.05). There were significant differences in FA ( P < 0.05) and ADC ( P < 0.05) between normal ACL and 3‐month graft postoperation, as well as in ADC values between 3‐month and 6‐month graft postoperation ( P < 0.05). Data Conclusion: DTI could be used to quantitatively evaluate the ACL injury grades and the development of ACL grafts. The diagnostic efficiency of FA values was higher than that of ADC values. Level of Evidence: 1 Technical Efficacy: Stage 3